ANALISIS MAKNA PESAN DAKWAH DALAM SYAIR LAGU KARYA ANREGURUTTA HAJI ABDURRAHMAN AMBO DALLE (SUATU KAJIAN SEMIOTIKA) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This research discusses the meaning of da'wah messages in the song lyrics by Anregurutta Haji Abdurrahman Ambo Dalle. The results show that the song by Anregurutta Haji Abdurrahman Ambo Dalle entitled Allahu Jalla, Sempajangnge, and Hubbul Malik was created based on the socio-cultural context behind it, namely 1) Allahu Song Jalla was based on the needs of society at that time which needed to be given an understanding of His attributes and to keep away from shirk; 2) The song Sempajangnge was created on the basis of many claiming to be faithful but not yet practicing Islamic law, especially the five daily prayers; 3) The background song of Hubbul Malik was a manifestation of strong nationalism in the context of fighting colonialism by strengthening nationalism. The three songs that are the object of this research are full of da'wah messages, both those related to faith, law, and morals, namely the song Allahu Jalla contains the message of akidah (knowing God and strengthening belief in Allah Almighty), the Sempajangnge song contains the message of sharia (related to with an explanation of prayer), the song Hubbul Malik contains a message of morality (morals to leaders and the right attitude in maintaining the integrity of the nation and state).